2016
DOI: 10.1055/s-0042-105205
|View full text |Cite
|
Sign up to set email alerts
|

Colonic transendoscopic enteral tubing: A novel way of transplanting fecal microbiota

Abstract: Background and study aims: Placement of a tube through the anus into the cecum has not yet been established as a method of administering whole-colonic treatment. The aim of this study was to evaluate the safety, feasibility, and value of transendoscopic enteral tubing (TET) for fecal microbiota transplantation (FMT) through the colon. Patients and methods: A prospective observational study was performed of FMT using a new colonic TET technique. Under endoscopic guidance, a TET tube was affixed to the cecum wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 14 publications
2
104
0
4
Order By: Relevance
“…Some of these investigated patients underwent FMT through TET technique, because the survey results may change since they experienced TET as colonic delivering way of FMT. [28] Additionally, this study only indicated the current attitudes of patients on FMT. With the improvement of human understanding on FMT, the patients’ attitudes may change in the future.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some of these investigated patients underwent FMT through TET technique, because the survey results may change since they experienced TET as colonic delivering way of FMT. [28] Additionally, this study only indicated the current attitudes of patients on FMT. With the improvement of human understanding on FMT, the patients’ attitudes may change in the future.…”
Section: Discussionmentioning
confidence: 98%
“…[12] On the contrary, none refused to accept the second FMT for the reason of poor aesthetics in this study. In our center, we performed FMT through mid-gut or colonic transendoscopic enteral tubing (TET), [28] which may improve the understanding of FMT and eliminate patients’ concerns about the aesthetics of FMT. It was expected that patients who were unwilling to receive the second FMT would also refuse recommending FMT to other patients.…”
Section: Discussionmentioning
confidence: 99%
“…The delivery technologies evolve continuously, aiming at both improving efficiency and increasing patient comfort. E.g., transendoscopic delivery to the cecum with pin-assisted tube fixation, and use of oral capsules are the most promising procedures now [19]. Another important question is the necessity of anesthesia upon delivery of donor's transplant.…”
Section: Donor Selection and Transplant Delivery Of Fecal Microbiotamentioning
confidence: 99%
“…Less invasive methods, such as retention enema and nasointestinal infusion, may be safer in patients who are frail or severely ill at the time of FMT. Transendoscopic enteral tubing for FMT through the colon has been reported by Peng et al40 Other methods of delivery through small intestine stoma or percutaneous endoscopic gastrojejunostomy have also been reported 40,41…”
Section: Introductionmentioning
confidence: 98%